Girlish gaiety: 1950s collectively-authored femininity in James Baldwin`s "Giovanni`s room" and the miss rheingold advertising campaign - Griffith, Terry; Hayes, Nicholas Alexander (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In "Giovanni`s room", james baldwin explores the contentious nature of american manhood and male sexuality. Baldwin uses depictions of womanhood to contrast and define the parameters of masculinity. The secondary character sue acts as a foil for the novel`s protagonist.
Keywords: femininity; advertisement; Miss Rheingold; Baldwin, James (1924-1987); "Giovanni`s room"